2014
DOI: 10.1039/c4ra11068d
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic control of Sb-rich Sb2Se3 to adjust its catalytic hydrogenation properties for p-nitrophenol

Abstract: Sb-rich Sb2Se3 with hollow sphere morphology is an efficient catalyst for the hydrogenation of p-nitrophenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In a typically catalytic procedure, p -nitrophenol aqueous solution (100 μL 0.025 mol/L) was mixed with 20 ml of deionized water, and the following procedures remain the same as our previous works [30]. …”
Section: Methodsmentioning
confidence: 99%
“…In a typically catalytic procedure, p -nitrophenol aqueous solution (100 μL 0.025 mol/L) was mixed with 20 ml of deionized water, and the following procedures remain the same as our previous works [30]. …”
Section: Methodsmentioning
confidence: 99%
“…From B-and C-film (Figure 1a), it was possible to verify a strong tendency for the formation of rods when the H 2 SeO 3 concentration in the electrolytic bath was increased in relation to the IC. [30] Therefore, we can conclude that it is convenient to maintain the bath with an Sb-rich composition (as the IC-bath). This change in morphology indicates that the concentration of Se in the bath greatly interferes with the film nucleation and growth kinetics.…”
Section: Effect Of the Precursor Concentration In The Electrolytic Bathmentioning
confidence: 99%
“…TANG et al had previously reported similar behaviour in the Se-rich samples when observing microrods from 100 to 300 nm in length obtained by a hydrothermal method using sodium borohydride as reductant. [30] Therefore, we can conclude that it is convenient to maintain the bath with an Sb-rich composition (as the IC-bath).…”
Section: Effect Of the Precursor Concentration In The Electrolytic Bathmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more emerging composites will offer a perspective for new entries into novel structures and high technology applications 15 23 . Sb 2 Se 3 , one of a typical 1D nanostructured material in the group V–VI binary semiconductors, has attracted considerable attention due to its unique photovoltaic 24 , electrochemical properties 25 and efficient catalytic performance 26 . The synthesis of Sb 2 Se 3 using facile hydrothermal or solvothermal method has been extensively studied 25 29 .…”
Section: Introductionmentioning
confidence: 99%